IDENTITY CLOSED IN IMAGES. ON LEKSYKON MIAST INTYMNYCH [INTIMATE TOWNS LEXICON] BY JURIY ANDRUKHOVYCH - Czyżak, Agnieszka (Porównania, 2014)
The article contains an interpretation of the atypical book written by Juriy Andruchovych in 2011 titled Leksykon miast intymnych (Intimate towns lexicon). The author decided to set his recollections in the alphabetical order by connecting all of the memories with descriptions of cities he had visited during his whole life. This idea enabled the writer not only to create pictures of the visited towns but also to describe the historical and cultural transformation of Central and Eastern Europe. Andruchovych was mostly interested in briging to life a picture of his own homeland, Ukraine, especially during the post-communist